A MULTI-CRITERIA DECISION ANALYSIS APPROACH TO PALLET SELECTION: DEVELOPMENT OF A MATERIAL-OF-CONSTRUCTION EVALUATION MODEL - Chama, Chama; Harding, Kevin; Mulopo, Jean; Chego, Paul (The South African Journal of Industrial Engineering, 2021)
Although pallets have traditionally been constructed from wood, there has been a shift towards making them from plastic and other composite materials. Subsequently, the storage and transportation industry has been inundated with questions about ‘the best’ pallet material type in relation to a supply chain. In addition, in a rapidly changing global manufacturing and storage environment, industry players have difficulty justifying the high capital cost of adopting new state-of-the-art pallets. This paper seeks to build a model to identify the best pallet material-of-construction (MOC) as perceived by the end consumer. The approach used for this was based on different stages of building an assistive multi-criteria decision model. This included modelling the decision framework using the analytic hierarchy process and undertaking an independent case study as the baseline for the modelling.